Interactional and convivial possibilities at war: Ukrainian students’ home-making on a multicultural campus (London Review of Education, 2024)
This article examines Ukrainian students’ home-making at London’s multilingual and multicultural universities, contrasting the ways in which students’ idea of themselves and their sense of belonging developed after their arrival in London, and the ways in which this experience was altered by the outbreak of war on 24 February 2022. For international students in the UK, making themselves at home on a university campus is a relational process in which cultural, linguistic and political ideas and practices, brought together from the students’ former homes, are negotiated and transcended in newly established social networks. In this article, we explore the ways in which students’ networks, old and new, are altered as a result of their experience of war. Our findings indicate that when imagined personal life trajectories are disrupted as a result of the social and political crisis that accompanies the war, the possibilities of articulating the individual experience and the social interactions that provide such affordances are existential processes, which allow (or not) individuals to (re-)engage in home-making and to find new meaning in their emplacement and sense of self.